OPTIMIZATION OF A WHOLE-BODY MAGNETIC RESONANCE IMAGING PROTOCOL FOR HODGKIN LYMPHOMA STAGING - A. I. Mikhaylov; V. O. Panov; I. E. Tyurin (Вестник рентгенологии и радиологии)
Objective: to optimize a whole-body magnetic resonance imaging (WBMRI) protocol including diffusion-weighted imaging (DWI) used as a diagnostic complex for Hodgkin lymphoma (HL).Material and methods. The WBMRI protocol adapted for HL staging and monitoring was tried out on 1.5 T and 3.0 T MRI scanners. The investigation included 128 patients with HL verified by complex clinical, laboratory, and instrumental studies (including computed tomography (CT), positron emission tomography (PET), PET/CT, scintigraphy and radiology of the skeleton, ultrasonography, laboratory tests, and biopsy) and 27 healthy individuals. The diagnostic value of the elaborated protocol was determined comparing with that of 18F-fluorodeoxyglucose PET, the gold standard for diagnosing HL in 63 patients with this condition.Results. WBMRI showed high sensitivity (99.2%) (97.6–100% confidence interval (CI)) and specificity (99.6%) (99.05–100% CI) in determining the foci of lesion in HL.Conclusion. The high sensitivity and specificity of WBMRI, which are similar to those of PET, may suggest that this method should be used to estimate the extent of the primary tumor in HL. Within one study, the proposed non-contrast-enhanced WBMRI protocol for 1.5 T and 3.0 T MRI scanners can yield anatomic (T2- WI) and functional (DWI estimating the measured diffusion coefficient) MR images of nodal and extranodal lesions in HL, without increasing time and modernizing equipment and software. The proposed protocol improves the quality of HL radiodiagnosis, by concurrently reducing a patient’s radiation exposure.